Peripheral human T cells sensitized in mixed leukocyte culture synthesize and express Ia-like antigens (The Rockefeller University Press, 1978)
We have studied the modulation of Ia-like antigens on the surface membrane of human T cells responding in a one-way mixed leukocyte culture. A heterologous antiserum, (anti-p23,30), which is specific to HLA-D-related antigens and which is unreactive with normal peripheral T cells or thymocytes, was found to bind significantly to all T cells transformed in mixed leukocyte culture (MLC) as determined by indirect immunofluorescence on a fluorescence-activated cell sorter 1. Furthermore, cytotoxic T cells responsible for cell-mediated lympholysis were shown to react with anti-p23,30, whereas their unactivated progenitors did not. Immunoprecipitation and sodium dodecyl sulfate polyacrylamide gel electrophoresis of a radioactive 29,000 and 34,000 dalton complex from MLC-primed T cells labeled with [35S]methionine indicated that allosensitized T cells synthesized these HLA-D-related antigens.